PENINGKATAN KETERAMPILAN PENULISAN CERPEN BERBASIS KEARIFAN LOKAL DENGAN TEKNIK PENGANDAIAN DIRI PADA SISWA KELAS VIII.A SMPN 1 TAPIN SELATAN KABUPATEN TAPIN TAHUN PELAJARAN 2020/2021 - zulkarnain (STKIP PGRI Banjarmasin, 2021)
Learning to write short stories is a written language skill with the aim of conveying ideas and ideas with creativity and imagination. The activity of writing short stories is one of the learning activities that are considered difficult and less fun for students. The aims of this study are as follows: (1) To describe the improvement of local wisdom short story writing skills with self-reliance techniques in VIII.A students of SMPN 1 Tapin Selatan (2) to describe the effect of changes in behavior of class VIII.A students of SMPN 1 Tapin Selatan in writing. short stories that are integrated with local wisdom with self-reliance techniques. It is hoped that this local wisdom base can help improve students' writing skills, especially short stories, which are related to students' daily lives, with cultural elements and local colors characteristic of Tapin Regency in particular, and South Kalimantan in general. This research is a classroom action research that uses two stages, namely cycle I and cycle II. The data of this study were obtained from test and non-test instruments. The test instrument data was obtained from the test results in the form of writing short stories, while the non-test instrument data was obtained from observations, diaries, interviews, and documentation. The data collected, both test and non-test were analyzed with qualitative and quantitative approaches. Based on data analysis, it can be concluded that writing short stories based on local wisdom with self-reliance techniques, students' skills in writing short stories increased by 19.6 or 29.07% from 67.72 in the first cycle to 85.13 in the second cycle. The behavior shown by the students also changed after being given action by the researcher. Students are more enthusiastic and more enthusiastic in writing, especially writing short stories.